Pengaruh Penggunaan Video Tutorial Berbasis Teknologi Informasi dan Modul Ajar Terhadap Peningkatan Keterampilan Dasar Siswa SMKN 3 Mataram - Hadi, Heri Sopian; Aranbi, Muhammad Defa; Supriatono, Herman; Isnain, M.Firdaus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the effect of using technology-based tutorial videos and teaching modules on improving the basic skills of students in the mechanical engineering program at SMK 3 Mataram. This research employs a quantitative approach with a quasi-experimental research design and a Nonequivalent Control Group Design. The study was conducted at SMK 3 Mataram with subjects from class X majoring in Mechanical Engineering, which is divided into two classes: Class X TPM (machining engineering) and Class X TPL (welding engineering), with data collection techniques gathered through pretests and posttests to measure the effect of the learning results before and after the treatment. Test results indicate that students who use video tutorials tend to achieve higher scores compared to those who only use teaching modules. This is because video tutorials are able to present material visually and auditorily, making it easier for students to understand abstract concepts and complex practical procedures.